A COMPARISON OF THE ROSE-WAALER, LATEX FIXATION, “RA-TEST,” AND BENTONITE FLOCCULATION TESTS - Greenbury, C. L. (1960)
The bentonite flocculation test of Bozicevich, Bunim, Freund, and Ward (1958), the latex fixation test of Singer and Plotz (1956), and the “RA-test” (a latex reagent for use as a slide test) of Hyland Laboratories have been compared with each other and with a modified Rose-Waaler test, the behaviour of which has been previously extensively investigated. In these tests sera from 2,250 patients were tested by two or more methods on 3,000 occasions. The findings of this trial are set out and the merits of the tests and reasons for disagreement among them are discussed. It is concluded that the most satisfactory means of testing rheumatoid sera is by the Rose-Waaler test and the “RA-test,” or a satisfactory modification of it, in parallel.